Hydranencephaly: A rare case report - Sharma, Nalini; Jante, Vinayak; Das, Rituparna; Panda, Subrat; Sagar, Mandeep (Indian Journal of Case Reports, 2021)
Hydranencephaly (HE) is a rare condition occurring in